Students' Scientific Literacy in Critical Thinking Skills in Science Learning: A Bibliometric Analysis from the Scopus Database - Lubis, Jalilah Azizah; Pantiwati, Yuni; Rahardjanto, Abdulkadir (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the trends, patterns, and dynamics of research on students' scientific literacy in relation to critical thinking skills in science learning through a bibliometric approach. The research seeks to identify dominant topics, international collaboration networks, and contributions from institutions and countries, as well as to explore the integration of scientific literacy with critical thinking skills in educational contexts. Data were collected from the Scopus database using keywords "students' scientific literacy and critical thinking skills", resulting in 68 articles after a rigorous screening process based on publication year (2019–2024). The analysis employed descriptive bibliometric methods, utilizing tool VOSviewer for mapping collaboration networks and research focus areas. The findings reveal a significant increase in publications, particularly in 2022 and 2024, Citation trends indicate that publications from 2019 had the highest impact, with 184 citations. International collaborations were dominated by countries with advanced education systems, such as the United States, Norway, and Taiwan, while developing countries like Indonesia and Malaysia showed active. Key research themes project-based learning (PjBL-STEM), socio-scientific issues, and the integration of local and spiritual values in science education.The study concludes that scientific literacy and critical thinking skills are increasingly recognized as essential competencies in education, with innovative pedagogical approaches playing a pivotal role in their development. The results provide valuable insights for researchers, educators, and policymakers to enhance curriculum design and teaching strategies. Future research should focus on specific contexts and interdisciplinary approaches to further explore the relationship between scientific literacy and critical thinking skills.